Abordagem multicritério participativa na escolha de influenciadores digitais em planejamento de marketing - Correia, Gabriela Colaço (Universidade Federal Rural do Semi-Árido, 2019)
Currently, as social networks play an important role in the decision-making of consumers. In this sense, digital influencers are tools for better reaching the marketing objectives of an organization. However, choosing the right digital technology for a business is a challenge for marketing departments as this type of decision is made intuitively and unstructured. The present study aims to propose a participatory approach for the selection of digital trends, and can be applied in different forms of companies. The following methodology is used: (i) establishment of a list with the main performance indicators, (ii) definition of the influencer evaluation results, (iv) ranking and (v) ranking analysis for the choice of the digital influencer, (vi) use of linear programming to establish optimal portfolio. The approach was tested and validated in a tourism company in Brazil. The alternatives named "A6" and "A3" were chosen in the proposed approach. It is highlighted that it is one of the options that are the contract with a studied organization, demonstrating a capacity of decision in representing the value judgment of the company. Thus, an approach has proved useful for companies that perform digital actions, having as a structured basis the choice of one of the most powerful digital motors in the marketing context.
Keywords: Influenciadores digitais; Abordagem multicritério de apoio à decisão; Marketing digital; Tomada de decisão; Planejamento de marketing; Digital influencers; Multicriteria approach to decision support; Digital marketing; Decision making; Marketing planning; ENGENHARIAS::ENGENHARIA DE PRODUCAO